Node.js web development - Herron, David (Packt Publishing, 2016)
Node.js is a server-side JavaScript platform using an event driven, non-blocking I/O model allowing users to build fast and scalable data-intensive applications running in real time. 'Node.js Web Development' shows JavaScript is not just for browser-side applications. It can be used for server-side web application development, real-time applications, microservices, and much more.